IMPLEMENTASI KEBIJAKAN PENGELOLAAN DANA DEKONSENTRASI PADA DINAS PENDIDIKAN DAERAH PROVINSI SULAWESI TENGAH - Djamalu, Abdul Haris (Katalogis, 2013)
The regulation of finance Minister 156/PMK/.07/2008 is the guideline in implementing De-concentration Budget Management and the supporting duty Budget. Therefore, this research aims to analyze the implementation of de- concentration budget management policy at the Regional Education Office of Central Sulawesi Province. This research employed qualitative method. To measure the implementation of that policy, the researcher adopted four indicators based on the theory of Edward III, namely communication, resources, disposition, and bureaucracy structure. The informants of this research were people who were involved in implementing the de-concentration budget management. Data consisted of primary and secondary data. Technique of data collection was interview, observation, and documentation. The data analysis dealt with three steps: data reduction, presentation, and conclusion. Based on data collection and analysis, this research result shows that the implementation of de-concentration budget management policy at the Regional Education Office of Central Sulawesi Province was not effective yet. In relation toÂ four aspects as the measurement instruments, the aspect of communication still had inadequate channels used to implement the policy, and inadequate the branches of bureaucracy structure. Besides, the regulation was still general, so the budget organizer should adopted another specific one. There was still unequal interest of each Ditjen; therefore, the consistence of the policy implementation was neglected. In the aspect of resources, the number of the staff was enough, but a few number of them had enough skill in organizing the budget. This was caused by the less opportunity of the staff to join education and training and their specific education background for budget management